Soil, bark and leaf trace metal loads related to the war legacy (The Prašnik rainforest, Croatia) (Rudarsko-geološko-naftni zbornik, 2016)
As a special forest vegetation reserve, the Prašnik rain forest is a highly protected area which owes its protection not only to a unique composition of trees, but also to its geographical position and, to an extent, historical events. It is situated on the Sava River left bank, north of the city of Stara Gradiška (cca. 3 km). The study area belongs to the southwestern part of Pannonian Basin, specifically the Sava Depression. The aim of this study was to assess a possible impact of war activities in Croatia (23 years ago) when numerous mines were laid in this region and to establish a major and trace metal baseline concentrations for future investigations. Ten topsoil (S) samples were taken randomly with adjacent vegetation (bark and leaves) at each site. Major and trace metal concentrations were measured for all three types of samples using the ICP method. Analysed soils are composed of quartz, micaceous mineral, 14Å mineral, plagioclase and mixed layer minerals. All metal values in the sample taken from an ex-mine crater are 2-4 times higher compared to other. Generally, positive statistically significant Kendall’s Tau correlation coefficients of trace metals (Cd, Cr, Cu, Ni, and Zn) were found for all combinations of the S (soil), B (bark), and L (leaf) groups. Such results indicate that the war activity have played a certain role in a distribution pattern of soil as well as vegetative trace metal levels.